2017
DOI: 10.1155/2017/3425108
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Color Marking of Titanium: A Modeling Study of the Interference Effect and the Impact of Protective Coating

Abstract: Laser-induced color marking of metals, due to numerous advantages, including inter alia the high quality, resolution, durability, and noncontact methodology of surface marking, seems to be attractive for use in various applications. In this method, the resulting color is mainly evident from the interference effect. Therefore, one of the still unsolved problems on titanium is the color change after imposition of an additional layer (fingerprints, grease, etc.). In this paper, a computer simulation based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Laser coloring was intensively investigated for ns pulse processing where oxide layers are formed [167][168][169][170]. Alternatively, ultra-short pulsed lasers can be used.…”
Section: Coloringmentioning
confidence: 99%
“…Laser coloring was intensively investigated for ns pulse processing where oxide layers are formed [167][168][169][170]. Alternatively, ultra-short pulsed lasers can be used.…”
Section: Coloringmentioning
confidence: 99%
“…As shown by several authors, 7 , 12 , 13 the laser texturing of a metallic surface in an oxygen-containing atmosphere does not result only in modified surface topography but also in surface oxidation. On a microscopic scale, this manifests as a change of surface color 13 , 14 and results in modified surface wettability. 15 17 After the laser texturing, the surfaces may become superhydrophilic in a saturated Wenzel regime (θ = 0°).…”
Section: Influence Of the Low-temperature Annealing On The Wettabilitmentioning
confidence: 99%
“…Again, they neglected the interference effects even though—as evident from the theoretical calculations in Figure 3 a, d—they should not be neglected. As explained in the section S9 of the Supporting Information , the reflectivity for an electric field in case of a double thin-film layer (DTF) system can be calculated as 14 where indices 1, 2, 3, and 4 stand for air, water, TiO 2 , and titanium, respectively (see Figure S32 ), and the phase change due to light propagation in water δ w is calculated similarly as phase change due to light propagation within the oxide film in eq 2 .…”
Section: Reflectivity Of the Laser-textured Metallic Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxide layer will repeatedly reflect the beam from the surface of both oxide and metal. Research by Łȩcka et al [3] said that the effect of colour can be observed and controlled if the oxide thicknesses on the surface are increased.…”
Section: Introductionmentioning
confidence: 99%